Morphology of macropores in n-Si formed in NH4 F-containing solutions during photoanodization - V. V. Bolotov; I. V. Ponomareva; K. E. Ivlev (Омский научный вестник)
The features of pore formation during photoanodization in electrolytes based on ammonium fluoride are studied depending on illumination, pH, current density. When comparing electrolytes with different pH (acidic and alkaline), a decrease in the pore diameter is observed at the same illumination and current densities in alkaline HF: NH4 OH solutions at a relatively equal etching rate in depth. In dilute HF: NH4 OH: H2 O under low illumination, there is a direct dissolution of silicon with the formation of a «starlike» pore morphology and a branching tendency. In the case of a concentrated solution of HF: NH4 OH 1: 4 branching is observed with increasing current density.